The teaching of environmental education and the genesis of institutional change in teaching practice in higher education institutions - Capponi, Neiva Feuser; Orsatto, Luís Felipe; Ahlert, Alvori; Dall’Asta, Denis (Seven Editora, 2023)
The higher education institutions (HEIs) were called to become the disseminators/spreaders of Environmental Education to their students, a subject that prompted this research, which analyses the genesis of the institutional change in the teaching practice related to Environmental Education at institutions of higher education. It is quantitative research, with descriptive analysis. A survey, forwarded through Google Forms, was prepared for professors associated with the area of the Applied Social Sciences from 2 HEI, one public and another private. The focus was on the institutionalization or not of Environmental Education in their teaching practices. The period used to conduct the survey was from August to October 2019, resulting in 30 responses, which after the analyses had the hypothesis H1 was validated, that is, EE is not yet institutionalized un HEIs, undermining the proposals of Federal Law 9.795/1999 and the State Law 17.505/2013 by encouraging the training of professionals/teachers, allowing in more professional/critical citizens to be placed in the job market annually, meeting the prerogatives of SDG4. DOI: https://doi.org/10.56238/devopinterscie-057